2001
DOI: 10.1007/s001250051625
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metabolism in streptozotocin-diabetic rats: an in vivo magnetic resonance spectroscopy study

Abstract: It is becoming increasingly clear that the brain is another site of diabetic end-organ damage [1]. Some diabetic patients develop cognitive deficits, which are generally moderate in young adults [2] but can be more pronounced in the elderly [3]. Recent epidemiological studies even report an association between diabetes and dementia [3,4]. Given the prevalence of diabetes among the elderly and the effect of cognitive impairment and dementia on the quality of life of patients and health care resources, a better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 50 publications
(92 reference statements)
3
29
1
4
Order By: Relevance
“…Early Metabolic Alterations at 4 Days Although there are a few previous in vivo 1 H-MRS studies that have investigated cerebral metabolic abnormalities in animal models of STZ-induced T1DM, [8][9][10]12 few of them measured metabolic changes in brain regions other than the hippocampus, nor at the time points earlier than 2 weeks after induction. In this study, we found that, under the hyperglycemia state, the STZtreated animals had significantly reduced tNAA/NAA levels in the striatum and hippocampus already at 4 days after induction.…”
Section: Discussionmentioning
confidence: 99%
“…Early Metabolic Alterations at 4 Days Although there are a few previous in vivo 1 H-MRS studies that have investigated cerebral metabolic abnormalities in animal models of STZ-induced T1DM, [8][9][10]12 few of them measured metabolic changes in brain regions other than the hippocampus, nor at the time points earlier than 2 weeks after induction. In this study, we found that, under the hyperglycemia state, the STZtreated animals had significantly reduced tNAA/NAA levels in the striatum and hippocampus already at 4 days after induction.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Most studies suggest that diabetes affects either the number or the function of central neurons, which is mirrored by a reduction in NAA levels and a lower NAA/Cr ratio. [4][5][6] Studies investigating the effects of diabetes on Cho metabolism have produced inconsistent results. Studies by Kreis and Ross 5 and Biessels et al 6 reported no difference in Cho/Cr ratios in diabetic rats or in brain tissue from patients with diabetes.…”
mentioning
confidence: 99%
“…[4][5][6] Studies investigating the effects of diabetes on Cho metabolism have produced inconsistent results. Studies by Kreis and Ross 5 and Biessels et al 6 reported no difference in Cho/Cr ratios in diabetic rats or in brain tissue from patients with diabetes. However, Sahin et al 7 found evidence of a lower Cho/Cr ratio in the parietal and frontal lobe white matter in patients with T2DM, which was inversely related to HbA1c levels.…”
mentioning
confidence: 99%
“…Our results, which imply decreased NAA levels, are consistent with those studying other neurological diseases, in either experimental animal models or humans, with associated neuronal damage. In a neurological study of streptozotocin-induced diabetic rats Biessels and coworkers [30] showed a decrease in both NAA/Cho and NAA/total Cr ratios 8 months after streptozotocin treatment. It was also found that cerebral NAA/Cr ratios were diffusely decreased in multiple sclerosis patients with early disease, a low demyelinating lesion load, and no significant disability [31].…”
Section: Discussionmentioning
confidence: 98%